Going Nowhere: Screendance and the Time of Dying - Macdonald, Anna (The International Journal of Screendance, 2017)
<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">This article considers a particular temporality—referred to as a state of moving stillness—within two different events: the screendance body that moves without appearing to get anywhere, and the dying body that moves but is not moving <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">to<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> anywhere. It focuses on <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Singing in the Rain<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> (1952) directed by Kelly and Donen and a practice as research screendance project, made by the author, entitled <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Walk<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> (2016). By placing events from art and life together here, alongside contemporary philosophies of temporality, the article works to illuminate something of the complex relationship between movement, time, and progression in each one, throwing light on the role that art, and screendance in particular, can play in our relationship to mortality.